TLR7/8 agonists trigger immunostimulatory properties of human 6-sulfo LacNAc dendritic cells - Jähnisch, Hanka; Wehner, Rebekka; Tunger, Antje; Kunze, Anja; Oehrl, Stephanie; Schäkel, Knut; Rohayem, Jacques; Bornhäuser, Martin; Tonn, Torsten; Bachmann, Michael; Schmitz, Marc (Cancer letters, 2013)
Imiquimod and resiquimod represent Toll-like receptor (TLR) 7 and 8 agonists, which emerged as attractive candidates for tumor therapy. To elucidate immune cells, which mainly contribute to TLR7/8-mediated antitumoral activity, we investigated the impact of imiquimod and resiquimod on native human 6-sulfo LacNAc (slan) dendritic cells (DCs). We found that both TLR7/8 agonists significantly improve the release of various proinflammatory cytokines by slanDCs and promote their tumor-directed cytotoxic activity. Furthermore, resiquimod efficiently augmented the ability of slanDCs to stimulate T cells and natural killer cells. These results indicate that imiquimod and resiquimod trigger various immunostimulatory properties of slanDCs, which may contribute to their antitumor effects.
Gesehen am 24.03.2021